PENERAPAN MODELPEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 010 KARYA MUKTI KECAMATAN RIMBA MELINTANG - Fateah, Siti; Marhadi, Hendri; Noviana, Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This Research is background overshadow by lowering of result of learning IPA of student of class of IV SD Negeri 010 Karya Mukti Kecamatan Rimba Melintang, with the class Mean 58,21. While complete value Kretiria Minimize the ( KKM) IPA is 68. Among/Between student amounting to 28 student only 7 one who reach the KKM. This Research represent the Research of Class Action ( PTK) done/conducted aim to to increase result of learning IPA of student of class of IV SD Negeri 010 Karya Mukti Kecamatan Rimba Melintang by applying model the study of co-operative of type TSTS. Instrument of data collecting of at this skripsi is sheet of activity perception learn and student and also result of learning. This Skripsi present the data of result of learning obtained from mean of result of learning before action 58,21 mounting to become 14,11% becoming 72,32 at cycle I. At cycle II mount to become 11,79% with the mean 84,11. Activity learn at first cycle I meeting obtain;get the percentage of equal to 62,20% with the good category, at second meeting experience of the improvement with the percentage 70,83% good category. Hereinafter first cycle II meeting of activity learn also experience of the improvement with the percentage 87,50 category very good and at second meeting of cycle II mount again with the percentage 91,67% category very good. while student activity of at first cycle I meeting obtain;get the percentage 54,17 with the category enough, at second meeting experience of the improvement with the percentage 66,67% with the good category, at this cycle is student start to comprehend the study activity with the applying model the study of co-operative of type TSTS marked with the student activity of at first pertemua of cycle of II of student activity experience of the improvement of equal to 79,17%, with the good category and at meeting. Result of research in class of IV SD Country 010 Masterpiece of Athwart Mukti Jungle Subdistrict prove that applying model the study of co-operative of type TSTS can improve the result learn the IPA of student of class of IV SD Negeri 010 Karya Mukti.Keyword : Model The Co-Operative of Type TSTS, Result of learning, PTK